2020
DOI: 10.3390/molecules25061464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Instant Controlled Pressure-Drop on the Non-Nutritional Compounds of Seeds and Sprouts of Common Black Bean (Phaseolus vulgaris L.)

Abstract: The common bean is an important caloric-protein food source. However, its nutritional value may be affected by the presence of non-nutritional compounds, which decrease the assimilation of some nutrients; however, at low concentrations, they show a beneficial effect. Germination and treatment by controlled pressure-drop (DIC, French acronym of Détente Instantanée Contrôlée) are methods that modify the concentration of these components. The objective of this work was to evaluate the change in the non-nutritiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
1
9
1
Order By: Relevance
“…The results obtained for total TPC coincide with those of Cardador-Martínez et al (2020), who reported a 1.5-times increase in black beans germinated for 7 days. (Oloyo, 2004) reported for germinated pea seeds similar values to those obtained in the present work.…”
Section: Quantification Of Tpc and Tfsupporting
confidence: 89%
See 1 more Smart Citation
“…The results obtained for total TPC coincide with those of Cardador-Martínez et al (2020), who reported a 1.5-times increase in black beans germinated for 7 days. (Oloyo, 2004) reported for germinated pea seeds similar values to those obtained in the present work.…”
Section: Quantification Of Tpc and Tfsupporting
confidence: 89%
“…pinto, a TF content increase from 10.87 to 70.06 mg CE/100 g dry matter, these values are higher than those reported herein, which could be due to the bean variety and its phenolic composition. Cardador-Martínez et al (2020) reported that the TF content of the black bean seeds increased from 16.2 to 35.5 mg CE/100 g dry matter during germination, whereas Ohanenye et al (2020) reported a reduction of TF of 28 and 64% in soy and peanut seeds respectively, after 5 days of germination. Similar results were obtained during germination of peas in this work (Table 1); this effect is due to the activity of the polyphenol oxidase that causes enzymatic hydrolysis of TPC and polymerization of TF during germination, giving rise to a significant reduction in TPC.…”
Section: Quantification Of Tpc and Tfmentioning
confidence: 99%
“…We must say that while a rich source of literature has shown antioxidant profiles in sprouts, little information is instead available about modifications of antinutrients profile during the germination process. For example, during the germination of common black beans, it was found that while trypsin inhibitors and phytates decrease, levels of phenols, saponins and tannins trend higher [265]. In the same study, the application of a Controlled Pressure-Drop demonstrates to further lowers trypsin inhibitors and extra raises saponin concentration, while it counters the decrease of phytates and the increase of phenols and tannins [265].…”
Section: Antinutrients and Allergens In Sproutsmentioning
confidence: 86%
“…For example, during the germination of common black beans, it was found that while trypsin inhibitors and phytates decrease, levels of phenols, saponins and tannins trend higher [265]. In the same study, the application of a Controlled Pressure-Drop demonstrates to further lowers trypsin inhibitors and extra raises saponin concentration, while it counters the decrease of phytates and the increase of phenols and tannins [265]. Since the biochemical characteristics of sprouted seeds are strictly related to sprouting conditions, different techniques, alone or in combination, could be performed to easily impact antinutritional levels.…”
Section: Antinutrients and Allergens In Sproutsmentioning
confidence: 99%
“…Currently, the study of the performance of DIC aims at the reduction or even elimination of food mycotoxins. Moreover, in purification operations, DIC is effective in the deodorization and desolvation processes [9,10], with interesting results on reducing non-nutritional and allergenic molecules [11,12]. Figure 1 summarizes the main applications of instant controlled pressure-drop technology in food processing.…”
Section: Introductionmentioning
confidence: 99%